Honduras: Agricultural R&D indicators factsheet - Stads, Gert-Jan; de los Santos, Luis (International Food Policy Research Institute, 2022)
Agricultural R&D expenditures in Honduras demonstrate considerable year-to-year fluctuations, not in the least due to the relatively short-term nature of donor funding on which some of the country’s principal agricultural R&D agencies are heavily dependent. In 2020, the country invested only 0.20 percent of its agricultural GDP in agricultural research, which is too low to effectively address farm productivity and other challenges of the rural poor. Given limited government support to agricultural R&D in Honduras, nongovernmental agencies play an important role in the country’s national agricultural research system. FHIA is the country’s largest agricultural R&D agency, and it is funded through a combination of interest from an endowment fund, donor contributions, and revenues from the provision of laboratory and other services. Despite a gradual increase in the number of agricultural researchers over the past decade, most Honduran researchers are only qualified to the BSc-level. Few researchers have PhD degrees, and many of those who do are approaching retirement age. Limited funding, along with few national postgraduate training programs, constrain the professional development of the large number of BSc-qualified researchers.